Cultivated Building Materials : Industrialized Natural Resources for Architecture and Construction - Hebel, Dirk E.; Heisel, Felix (Birkhäuser, 2017)
NEXT GENERATION BUILDING MATERIALS The 21st century faces a radical change in how we produce construction materials - a shift towards cultivating, breeding, raising, farming, or growing future resources. This book presents innovative industrialized production methods for cultivated building materials, like cement grown by bacteria, bricks made of mushroom mycelium, or bamboo fibers as reinforcement for concrete. Spanning from scientific research to product development and architectural application, this book builds a bridge between the academic and the professional world of architecture. The book describes the challenges, strategies, and goals in the first part, followed by a second part on bamboo, A cultivated building material and a number of examples in the third part which form the bridge from cultivated materials to building products.